Carbon nanotube encapsulated metal selenide nanostructures for efficient electrocatalytic oxygen evolution reaction. Issue 60 (6th July 2022) - Singh, Harish; Liyanage, Wipula P. R.; Nath, Manashi
Abstract : Nickel selenide nanowires grown inside carbon nanotubes through in situ encapsulation via one-step chemical vapor deposition exhibit highly efficient electrocatalytic activity for oxygen evolution reaction. Abstract : Nickel selenide nanowires were grown inside carbon nanotubes through in situ encapsulation via one-step chemical vapor deposition. These NiSe2 @CNT nanohybrids showed excellent electrocatalytic activity for water splitting with a low overpotential of 260 mV at 10 mA cm −2, high current density, and extended stability owing to the synergistic effect between NiSe2 and CNTs.